The artistic and philosophical content of the problematique of rebellion in the works of Oles Ulianenko - Shteinbuk, Feliks (Slavia Centralis, 2023)
The author of the article set himself the goal of examining the literary works of Oles Ulianenko, an outstanding Ukrainian writer, applying the hermeneutic and comparative typological methods in view of the problem of rebellion represented in the novels. The analysis of the writer’s works was based on the philosophical doctrines of F. Nietzsche and A. Camus, who defined rebellion as a person’s right to deny the injustice of their absurd existence, which was not only a politically conditioned act but also a metaphysically grounded act. Thus, the artistic and philosophical meaning of the problem of rebellion, realised in the work of Ulianenko, depicts the rebellious intentions of the characters of the novels that seem to be expecting that their extraordinary protest potential will finally be channelled into the productive and worthy direction of struggling for universal freedom.